Peran Mahasiswa KKN Dan Masyarakat Dalam Membangun Semangat Gotong Royong Di Perumahan Pematang Indah RT 18 - Falentino, Feby; Hidayat, Rahmat; Cahya, Andika; Afrijal, Gustian; Putriani, Ririn; Kresnawati, Kresnawati; Suwarni, Suwarni; Soleh, Ahmad (Jurnal Gotong Royong, 2025)
The mutual cooperation program in RT 18 RW 02 in Pematang Indah Housing has been successfully implemented by students of the Community Service Program (KKN). Despite facing several obstacles, good collaboration between students and the community has made it possible to achieve positive result. This mutual cooperation activity includes enviromental cleanliness, overcoming garbage problems, clogged, gutters, and creating awareness of the importance of cleanliness. In addition to providing physical inpacts, this program also forms a familly relationship between students and resident of Pemaang Indah housing. Active community involvementt is key to achieving the success of this program. This mutual cooperation program is a learning event for studentsin developing social and leadership skills. It is hoped that the success of this program can be an inspiring example for the next KKN activities and continue to provide positif contributions to society and the environment.